Pengaruh PMA, PMDN dan Tenaga Kerja Terhadap PDRB Sektor Industri Pengolahan di Kota Pekanbaru - Nabilla Zulfi; Mardiana Mardiana; Ufira Isbah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to determine whether there is an effect of FDI, Domestic Investment, and Labor on the GRDP of the Manufacturing Industry Sector in Pekanbaru City. This study uses independent variables such as FDI, Domestic Investment, and Labor with the dependent variable being the GRDP of the Manufacturing Industry Sector in Pekanbaru City. The data used in this study consisted of 2012 to 2024. The method used in the analysis approach is descriptive quantitative, and tested with multiple linear regression using SPSS 26 software.The results of the study indicate that, based on simultaneous regression analysis, FDI, Domestic Investment, and Labor have a significant impact on the GRDP of the Manufacturing Sector in Pekanbaru City. Partially, the Domestic Investment and Labor variables have a positive and statistically significant influence on the GRDP of the Manufacturing Industry Sector in Pekanbaru City, while the FDI variable has a positive and statistically insignificant influence on the GRDP of the Manufacturing Industry Sector in Pekanbaru City